Does the New Proposal for Prostate Cancer Grading Correlate With CAPRA Score? - Isikay, Levent; Tonyali, Senol; Aydog, Gulden (Urology Journal, 2018)
Purpose: To determine if there is a correlation between the newly proposed Gleason grading system by the International Society of Urological Pathology and the Cancer of the Prostate Risk Assessment (CAPRA) score. Material and Methods: The records of all patients that underwent radical prostatectomy at our hospital between 2007 and 2013 were retrospectively reviewed. The study parameters included patient demographics, the percentage of pre-operative prostate biopsies positive for PCa, biopsy Gleason Score (GS), and pre- and post-operative PSA values. Result: The study included 146 patients with complete medical records and follow-up data. Mean age of the patients was 66.6 ± 6.08 years. According to the newly proposed Gleason grading system, 97 (66.4%) patients were grade 1, 20 (13.7%) were grade 2, 8 (5.5%) were grade 3, 11 (7.5%) were grade 4, and 10 (6.8%) were grade 5. The distribution of CAPRA scores was as follows: 1: n = 43 (29.5%); 2: n = 53 (36.3%); 3: n = 22 (15.1%); 4: n = 14 (9.6%); 5: n = 8 (5.5%); 6: n = 4 (2.7%); 7: n = 1 (0.7%); 8: n = 1 (0.7%). Correlation analysis showed that the CAPRA score was significantly correlated with GS based on the newly proposed Gleason grading system (Correlation Coefficient=0.361, P < 0.001). Conclusion: As a strong correlation was noted between these 2 independent grading systems, we think clinicians that seek to predict the prognosis in PCa patients should take into consideration both the newly proposed ISUP grading system and the CAPRA score.